Study of laparoscopic repair of hiatus hernia - D. Sagrule, Dhiraj; M. Lanjewar, Sunil; N. Gajbhiye, Raj; Nadagawali, Vishal (International Surgery Journal, 2017)
Background: Traditionally, repair of giant PEH has been performed through an open laparotomy or thoracotomy. This population of patients is often elderly, with comorbidities, which has led to concern over surgical referral. With the advent of laparoscopy, giant PEHs are now being approached with minimally invasive techniques. Less invasive procedures may decrease the amount of postoperative pain and the perioperative complication rate and shorten recovery time. Recently, a few series have reported that laparoscopic repair of PEH is technically feasible, effective, and safe. Thus, once paraoesophageal hernia is identified current thinking is that it should be surgically treated regardless of symptoms. Methods: Prospective study of patients diagnosed with hiatus hernia on endoscopy and barium swallow was conducted from October 2010 to November 2013. All patients with consent were operated with standard laparoscopic Nissens fundoplication and some require crural repair and studied during the course. Results: 22 cases with haitus hernia type I 8 (36.41%), type II 7 (31.8%) and type III 7 (31.8%), 68.18% having heart burn, 54.55% regurgitation, dysphagia 36.36% and chest pain 31.82% were treated and observed preoperative, intraoperative and postoperative. Most cases 15 (68.18%) were between 61-70 years age group with 13 (59.09%) males and 9 (40.91%) females. 9.9% had asthma, 13.64% DM and 36.36% systemic HT out of 22 cases. Mean blood loss was 29.09 ml, mean operative time was 181.27±8.80 minutes, mean hospital stay was 3.68 days with 4.55% intraoperative complication, 4.55% postop complication rate having mean VAS on post op day 1 was 6.31 and on day 7 it was 0.52.